2018
DOI: 10.1542/peds.2018-0341
|View full text |Cite
|
Sign up to set email alerts
|

Social Aspects of Hookah Smoking Among US Youth

Abstract: BACKGROUND:We investigated 3 social dimensions of youth hookah smoking: frequency, places smoked, and descriptive social norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
(8 reference statements)
0
13
0
Order By: Relevance
“…Hookah use among US youth population in schools was under scrutiny in many studies. For instance, one study surveyed a representative sample of 6th–12th grade students for hookah use, and the results showed that 10.5% reported smoking hookah [48]. Another study documented that hookah “ever use” among middle and high school students in USA included 6.8–15% of the students [31].…”
Section: Reasons and Prevalence Of Hookah Usementioning
confidence: 99%
“…Hookah use among US youth population in schools was under scrutiny in many studies. For instance, one study surveyed a representative sample of 6th–12th grade students for hookah use, and the results showed that 10.5% reported smoking hookah [48]. Another study documented that hookah “ever use” among middle and high school students in USA included 6.8–15% of the students [31].…”
Section: Reasons and Prevalence Of Hookah Usementioning
confidence: 99%
“…For example, high rates of discontinuing product use were common for hookah, ENDS and cigars as reported by Stanton et al 37 and Edwards et al 38. Use of tobacco products such as hookah and ENDS is more common among young adults, who experiment with tobacco products and use them infrequently 39–41. These products may be driven by similar motivational factors like socialising in hookah bars and vape shops, availability of appealing flavours, beliefs that these products could be less harmful than cigarette smoking and by pervasive misconceptions that products like hookah have low probability of addiction and quitting is not as difficult 1 36.…”
Section: Discussionmentioning
confidence: 96%
“…Homes represent a social setting where WPT smoking frequently takes place. [38][39][40][41][42][43] We previously found that WPT smokers smoke at home to relax comfortably, eat and drink while smoking and save money by not going to hookah lounges/ cafés. 39 To our knowledge, this is the first study to quantify postsmoking WPT waste and describe post-smoking WP device cleaning practices and disposal of waste associated with WPT use in natural home settings.…”
Section: Introductionmentioning
confidence: 99%